Media Social Marketing terhadap Brand Awareness, Brand Image dan Niat mendaftarkan Anak ke Go Power Kids - Diego Muhamad Alkhadaf; Sri Hartini (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the influence of social media marketing on brand awareness, brand image, and purchase intention, as well as analyzing the relationship between brand awareness, brand image, and purchase intention on gopowerkids.id Instagram followers. This research uses the Partial Least Squares (PLS) Structural Equation Modeling (SEM) analysis method with a population of respondents who are Instagram followers of gopowerkids.id. A total of 85 respondents were selected using purposive sampling technique. Data was collected through the use of questionnaires distributed to respondents. The results of data analysis show that social media marketing has a significant influence on increasing brand awareness, brand image and purchase intention. Apart from that, it was found that brand awareness also has a significant influence on purchase intention, as well as brand image. These findings show that social media marketing has an important role in increasing brand awareness, brand image and purchase intention among gopowerkids.id Instagram followers. The conclusion is that social media marketing has a significant impact in shaping consumer perceptions of brands, as well as influencing their purchasing intentions. Therefore, companies need to pay close attention to marketing strategies via social media to strengthen brand awareness, build a positive brand image, and increase consumer purchasing intentions. Keywords: Brand Image, Brand Awareness, Purchase Intention, Social Media Marketing